Cluster-based and Diamond Model Analysis of Herbal City in Thailand: A Case Study of Surin Province - Kungwansupaphan, Chonnatcha; Suwannapusit, Ubonwan (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 4 (2024): October - December 2024, 2024)
Clusters are a crucial component that helps create differentiation and competitiveness within industries at both the national and provincial levels in Thailand. This study aims to identify the components and the details of herbal cluster, and assessing the competitiveness of the herbal sector by applying the diamond model concepts in Surin province, recognized as the herbal city of Thailand. This study utilized a qualitative approach, conducting semi-structured interviews with 27 key informants selected based on their expertise or involvement in the development of the herbal sector in Surin province. The findings reveal that Surin province has elements of the diamond model, which include both factors that provide advantages and factors that hinder the development of the herbal sector in the province. Advantageous factors include natural resources, traditional herbal knowledge, the expanding and growing herbal market, a supporting business structure in the herbal sector, as well as numerous government agencies, private organizations, and supporting industries for herbal development. In contrast, several obstacles consist of the production management of herbs from upstream to downstream, business strategies to meet consumer demands, a well-integrated network system in the herbal sector, and inconsistency in policies and promotions by governmental agencies. To enhance the competitiveness of the herbal sector, policy recommendations are drawn to take immediate action to improve conditions in disadvantaged dimensions in the model. Keywords: Cluster, Diamond Model, Herbal City, Surin Province